2018
DOI: 10.3389/fpsyt.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Larger Gray Matter Volume in the Basal Ganglia of Heavy Cannabis Users Detected by Voxel-Based Morphometry and Subcortical Volumetric Analysis

Abstract: Background: Structural imaging studies of cannabis users have found evidence of both cortical and subcortical volume reductions, especially in cannabinoid receptor-rich regions such as the hippocampus and amygdala. However, the findings have not been consistent. In the present study, we examined a sample of adult heavy cannabis users without other substance abuse to determine whether long-term use is associated with brain structural changes, especially in the subcortical regions.Method: We compared the gray ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
4
18
0
Order By: Relevance
“…adult males with ADHD in Community 1 and Community 4 more frequently reported comorbidities than those in the other two communities, in particular mood disorder and SUD. Community 1 and Community 4 were characterized by relatively larger basal ganglia across the entire sample, which may be consistent with a previous study reporting increased basal ganglia volume in long-term substance abusers (30). The lack of significant associations with symptom severity and the limited findings for comorbidities may be due to insufficient power of the analyses in individual communities.…”
Section: Discussionsupporting
confidence: 88%
“…adult males with ADHD in Community 1 and Community 4 more frequently reported comorbidities than those in the other two communities, in particular mood disorder and SUD. Community 1 and Community 4 were characterized by relatively larger basal ganglia across the entire sample, which may be consistent with a previous study reporting increased basal ganglia volume in long-term substance abusers (30). The lack of significant associations with symptom severity and the limited findings for comorbidities may be due to insufficient power of the analyses in individual communities.…”
Section: Discussionsupporting
confidence: 88%
“…Assessments of brain regions other than the hippocampus have revealed disparate results. Several reports found no group differences in amygdala volume (43,(58)(59)(60)(61)(62), but according to one report, the amygdala was 7.1% smaller in users than in controls (47). A large study of 22-35-year-old participants (483 in all, 282 reporting having ever used cannabis) found smaller left amygdala and right ventral striatum volumes; but the differences were within the range of normal variation, and the apparent effect on amygdala was largely attributed to shared genetic factors (63).…”
Section: Effects On Brain Structurementioning
confidence: 97%
“…Furthermore, although we have excluded participants reporting psychoactive medication use and other illegal drug consumption, a formal urine toxicology screen was not performed. Lastly, it should be noted that abnormalities in grey matter have been reported in PCU, especially in long-term heavy cannabis users [9]. Therefore, although we have investigated young adults with PCU, it cannot completely be excluded that structural alterations might affect the forward modeling by means of different conduction delays and cortical thickness.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, structural neuroimaging studies showed abnormalities in hippocampus volume and gray matter density associated with cannabis use [8]. Furthermore, Moreno-Alcázar et al [9] recently reported that, compared to healthy controls, long-term heavy cannabis users showed increased gray matter volume in the basal ganglia and nucleus accumbens. A recent meta-analysis [3] on 35 task-related functional imaging studies also showed that cannabis use is associated with a decreased activity in brain areas involved in cognitive control process (e.g., the anterior cingulate cortex and dorsolateral prefrontal cortex (dlPFC)) and increased activity in brain structures involved in reward processing (e.g., the striatum).…”
Section: Introductionmentioning
confidence: 99%